Interior Design of AGHE Coffee & Resto with a Green Design Theme Through the Exploration of Sensory Experiences of the Five Senses - Pradana, Albertus Agung Paskah; Agung Purnomo, Agung; Heriwati, Sri Hesti (Pendhapa, 2023)
The interior design of AGHE Coffee & Resto, with a Green Design theme through the exploration of sensory experiences of the five senses, aims to create a unique design for AGHE Coffee & Resto that offers a distinctive experience to visitors through various stimuli received by the senses. The approach adopted in this design encompasses the themes of green design and industrial style as functional and ergonomic considerations. The design methodology employs Kurtz's programming method of orientation, base program, iterative programming, and design as feedback. The outcome is an interior design for AGHE Coffee & Resto that provides a novel sensation to space users through various stimuli the five senses receive. The scope of this design covers areas including the lobby and bar, guest waiting area, dining and drinking space, food storage area, employee space, kitchen, office, restroom, and prayer room. A distinctive advantage of this design is its focus on senses other than vision, which often gets sidelined in interior design projects.